The Effect of Picture and Picture Interactive Model to Increase Student’s Learning Motivation in Elementary Science Learning - Aini Wira Dharma Putri; Enik Setiyawati (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This research aims to determine the influence of the interactive picture and picture learning model on improving students' learning motivation in elementary school science. The author used quantitative research, which involved the entire class V A population at Oro-Oro Ombo Wetan 1 Elementary School in the academic year 2022-2023. The research method used was Pre Experimental Design with a non-pure experimental model (one-shot case study). Data collection was conducted using a questionnaire to measure the increase in students' learning motivation in class V A. For data analysis, the independent variable (x) was the interactive picture and picture learning model, while the dependent variable (y) was the improvement in students' learning motivation. The analysis used was the one-sample t-test, with a significance level of 5% (0.05), resulting in a significant t-value (2-tailed) of 0.006. Therefore, the obtained significance value of t 0.006 < 0.05 means that the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. Hence, there is an influence of the interactive picture and picture model on improving students' learning motivation in elementary school science at Oro-Oro Ombo Wetan 1 Elementary School in class V A.